THE INFLUENCE OF INTERNATIONAL COOPERATION ON THE FISCAL EFFICIENCY OF THE TAXATION SYSTEM OF UKRAINE - Кульчицька, Надія; Дерманська, Людмила; Поляк-Свергун, Марʼяна (SWorldJournal, 2024)
The article examines the role of state administration in the economic development of Ukraine through the improvement of the investment climate and the tax system. Considerable attention is paid to Ukraine's participation in international organizations, su